On a Miniature Free-Swimming Robotic Fish with Multiple Sensors. (1st April 2016) - Yu, Junzhi; Chen, Shifeng; Wu, Zhengxing; Wang, Weibing
Bio-inspired robotic fish hold strong promise for underwater missions. This paper deals with the design and control issues of a miniature free-swimming robotic fish with multiple sensors. Specifically, a synthesized mechanical design scheme mainly relying on a two-link serial mechanism and a pair of mechanical pectoral fins is first presented. Next, a bio-inspired Central Pattern Generator (CPG) based control method aided by feedback information from multiple sensors of various types to achieve three-dimensional swimming is proposed. Finally, experimental results on the 35-centimetre-long robotic fish verify the efficacy of the proposed mechatronic design and control methods. It is found that the CPG control combined with sensory information greatly contributes to swimming ability and intelligence of the robotic fish.